(3eXgQ GdJbOjS HPgGH OhdI GdaQfSjSs - (3YHO GdQMef Hf MSf GdLHQJj GdeUQj GdMfaj,J (B1237 (3g` s
(3ChdgG (B:s
(3MeOkG def LYd cdeI GdPjf caQhG GdSadi hcdeI Gddg gj GdoYdjG s
(3UOQg HebOeg oeNJUQI ai JGQjN eUQs
(3fSNI KGfjIs
(3hVe Edjg RjGOGJ eeG febg eYGUQg hUGMHg GdYdGeg GdTjN MSf GdYWGQ haQZ ef JCdjag SI (B1216 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B304 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B133s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B730 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B146 s
Keywords: (3GdJGQjNs